Analysis and Simulation of a Fractional Order Optimal Control Model for HBV - Liangli Yang; Yongmei Su; Xiaoke Li; Yongan Ye (Journal of Function Spaces)
In this paper, we propose a fractional optimal control model of anti-HBV infection based on saturation incidence and logistic proliferation of uninfected cells for the first time. We derive the basic reproduction number R0 and the cytotoxic T lymphocyte immune response reproductive number R1 and give the stable analysis based on R0 and R1. We analyse the optimal control condition and give two optimal control strategies about entecavir monotherapy and combination therapy of traditional Chinese medicine and entecavir with different fractional orders by simulation. The simulation shows that combination therapy may be a good choice in anti-HBV infection therapy. We also compare the objective function values of the optimal control strategies with other constant control strategies; the comparison shows that the optimal therapy can get similar or better treatment effect with less drug dose and side effects.